2015
DOI: 10.1021/acs.jafc.5b04109
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Gelation Mechanism of Freeze–Thawed Hen Egg Yolk

Abstract: A study of yolks stored up to 168 d at −20 °C was conducted to determine the gelation behavior and mechanism of freeze–thawed yolk. Methods used were rheology, native and sodium dodecyl sulfate polyacrylamide gel electrophoresis (native- and SDS-PAGE), differential scanning calorimetry (DSC), transmission electron microscopy (TEM), particle size analysis, and proton nuclear magnetic resonance (1H NMR) spectroscopy for matrix mobility. Results indicate that both constituents of plasma and granules contributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 79 publications
2
28
0
1
Order By: Relevance
“…Most researchers have focused on understanding the mechanism of egg yolk gelation and looked for different methods to prevent it [8,[10][11][12][13]. Au et al [10] experimented with freezing egg yolk at −20 • C for 168 days and studied the gelation process and kinetics. Both plasma and granules were found to be involved in the gelation process [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most researchers have focused on understanding the mechanism of egg yolk gelation and looked for different methods to prevent it [8,[10][11][12][13]. Au et al [10] experimented with freezing egg yolk at −20 • C for 168 days and studied the gelation process and kinetics. Both plasma and granules were found to be involved in the gelation process [10].…”
Section: Introductionmentioning
confidence: 99%
“…Au et al [10] experimented with freezing egg yolk at −20 • C for 168 days and studied the gelation process and kinetics. Both plasma and granules were found to be involved in the gelation process [10]. Primacella et al [8] concluded that all low-density lipoprotein, high-density lipoprotein, and livetins were also involved in the egg yolk gelation process.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudios han demostrado que la yema de huevo en bajos porcentajes es muy considerada en la criopreservación debido a su composición de lípidos, proteínas y apopoliproteínas, las cuales pueden formar agregados dentro de una consistencia gelatinosa provocada por el plasma y los gránulos, a temperaturas de congelación, evitando la formación de cristales en las primeras etapas del congelamiento (Au et al, 2015). Este aditivo ha sido empleado en la criopreservación de esperma de pez gato africano (Clarias gariepinus) mostrando una alta tasa de fertilización y de eclosión (Muchlisin et al, 2015).…”
Section: Discussionunclassified
“…For EYP’s gelation, we selected freeze-thaw gelation over other methods [21,54,55] because of its ease; most labs possess −20 °C freezers. In line with our systems physiological needs, the rheometer conducted the viscoelastic tests at 37 °C, contrasting other food science studies [25,26,27,28,29,30,31]. Alternative to shear, compression tests have often measured soft tissue stiffness values and identify a tissue’s tensile storage modulus E’ (in Pa).…”
Section: Discussionmentioning
confidence: 99%
“…Additional data from other angles of view and techniques could provide us with more information on human cell behaviour in egg-derived biomaterials. As for EYP’s gelation for 3D cultures or 3D-Bioprinting applications, several food science reports have investigated EY and EYP’s gelation [25,26,27,28,29,30,31] and proposed theories on the mechanism of freeze-thaw gelation [25,27,28,29,30,31,32]. To create gelled EYP ( G EYP), the literature has reported optimal freeze-thaw gelation of EYP between −12 [28] and −21 °C [32].…”
Section: Introductionmentioning
confidence: 99%